(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The relative strength index (RSI) is one of the best known technical analysis indicators; it provides the speculators by prior signals about the future stock’s prices, and because the speculations in shares of companies which listed in the Iraq Stock Exchange have a high degree of risk, like risk of shares prices felling, so the speculators became committed to use some methods to reduce these risks, and one of these methods is the technical analysis by using the relative strength index (RSI) which enable the speculators of choosing the right time for buy and sell the stocks and the right time to enter or leave the market by using the historical rice data. And from here the problem of the research formulated as “Is the using of the relative strength index (RSI) reduce the risks of speculation decision of shares in the Iraq Stock Exchange”. The research aims to present the role of technical analysis by using the relative strength index in reducing the risks of speculation decision of shares in the Iraq Stock Exchange. It is found in this research that the using of the relative strength index has reduced the risks of speculation decision of shares in Iraq Stock Exchange; it helped the speculators in making the buying and selling decisions in the right time by providing them with a proactive signals.